Haematinic and Hepatoprotective Properties of Telfairia occidentalis Fruit Mesocarp on Phenylhydrazine-Induced Anaemia in Experimental Rats - Ada Francesca Nneoyi-Egbe; Eridiong Onyenweaku; Andyno Akpanukoh; Patricia Ebai (Biochemistry Research International)
The level and potential of iron contained in fluted pumpkin (Telfairia occidentalis) has been exploited as a blood tonic; however, the potentials of some other parts of the plant are unknown. The effect of T. occidentalis fruit mesocarp (aqueous extract) on phenylhydrazine (PHZ)-induced anaemia in experimental rats was investigated in a bid to determine its curative properties and potential in reversing haemolytic anaemia and protection of liver health. The LD50 of the fruit extract was determined using Lorke’s method for the determination of acute toxicity. The study involved oral administration of varying doses of the extract to different groups of rats which were monitored for 24 hours. The test sample did not show any signs of toxicity at doses of 5000 mg/kg b.wt, which is the highest possible recommended dose for toxicity testing. For the evaluation of the effects of the fruit extract on haematological indices and biochemical enzyme markers in anaemic rats, 30 matured albino Wistar rats were used. The rats were divided into five groups of six rats each. Group 1 consisted of normal rats (control group), Group 2 consisted of anaemic untreated rats, and Group 3 consisted of anaemic rats treated with the standard drug Astymin, while Groups 4 and 5 were made up of anaemic rats given the extract at doses of 600 mg/kg b.wt and 1000 mg/kg b.wt, respectively. The fruit extract failed to show any significant effect in improving the haemoglobin (Hb), alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphate (ALP) levels in anaemic rats but rather may have contributed to a reduction in Hb levels and an unhealthy increase in serum enzyme levels. This is indicative of the apparent inability of the aqueous extract of the T. occidentalis fruit mesocarp to reverse PHZ-induced haemolytic anaemia and may suggest a possible detrimental effect of high doses of the extract over a prolonged period.